An idea of public reason: exclusionary and broad - Diogo Fernandes (International Journal of Philosophy and Social Values)
Any conception of public reason that includes a principle of restraint on certain kinds of reasons, making them inadmissible for the purposes of public political justification, has to be specified according to the following characteristics: 1) the admission of reasons other than those which are part of its content, in which case it can be distinguished as to its exclusivity or inclusivity; and 2) the object of its application – only the basic structure of society or something beyond it – in which case it can be distinguished as to its limits. I will defend an idea of public reason characterized as exclusionary and broad, not admitting reasons that do not belong to the public political culture of pluralist democracies and extending to all matters involving the coercive power of the state. Against an inclusive perspective, I will argue that the fears related to the lack of authenticity of public political discourse are not only unfounded, but that the exclusionary view contributes better to fix the duty of neutral justification in the public political culture. Against a narrow perspective, I will argue that the incompleteness of public reason cannot be determined a priori, and that its limitation to the basic structure is inconsistent with the conditions of reasonable disagreement.